Synthesis of 7-methyl-6-indolopterin and 7-methyl-6-indoloquinoxaline. Issue 18 (16th September 2016) - Goswami, Shyamaprosad; Das, Manas Kumar; Maity, Annada C.; Quah, Ching Kheng; Fun, Hoong-Kun
ABSTRACT: The first syntheses of indolopterin and indoloquinoxaline, two important and dissimilar diheterocycles linking C-2 of indole with C-6 of pterin (significant positions for showing biological activity), and quinoxaline, respectively, have been achieved based on two classical reactions. The introduction of a keto methyl group on to the 6-position of pterin and quinoxaline followed by Fischer indole synthesis led to these target diheterocycles. These indole-substituted diheterocycles will significantly increase the electron density on the pterin-5-N and quinoxazoline-2-N, which may change the redox properties of pterin and quinoxaline, and also the electron-withdrawing pterin or quinoxazoline should make the indole NH more acidic. GRAPHICAL ABSTRACT: